Propuesta didáctica: Palpando la realidad del patrimonio cultural - Chaverri Flores, Laura (2013)
The course National Reality Seminar II, Cultural Heritage, at the General Studies School at the University of Costa Rica highlighted some cultural weaknesses such as the lack of knowledge and appreciation of di- fferent cultural heritages of our country. For this reason the teaching strategy Feeling the Reality of Cultural Heritage was proposed, with the intent that students succeed in becoming involved with the reality of the national heritage and have better contact with it through the analysis of heritage sites without conforming to a descriptive study but rather by engaging with patrimony’s current problems and the status of assets. The strategy included 5 specific actions of different duration. Actions 1 and 2 consisted of two walks and tours, one to our capital and the other to Turrialba, and were focused on emphasizing our tangible and intangible heritage. Action 3 proposed visits and contact with the assets chosen by teams of 4 students each. Action 4 led to the creation and production of a poster in which the teams were able to creatively show the importance of their choice. Finally action 5 consisted of the production of a magazine by the whole group. The tasks that the instructor performed prior to the strategy were preparation, research and advice, whereas the students had a proactive role. The evaluation results of the course were quite positive as most students valued it qualitatively and quantitatively with the highest scores.